Expression of Recombinant Sugarcane Streak Mosaic Virus Coat Protein Gene in Escherichia coli - Hamdayanty Hamdayanty; Sri Hendrastuti Hidayat; Tri Asmira Damayanti (Bogor Agricultural University, Indonesia, 2016)
Sugarcane streak mosaic virus (SCSMV) is an important virus causing mosaic disease in sugarcane and transmitted through the cutting cane. Commercial antiserum to detect SCSMV and to monitor the disease development is not available. The research was conducted to produce antigen of SCSMV coat protein (SCSMV-CP) through overexpressing it on bacterial expression which will be used for antiserum production. SCSMV-CP was amplified using specific primers for CP gene containing BamHI and HindIII restriction enzyme sites and cloned into pTZ57R/T. Subsequently, the SCSMV-CP was subcloned into pET28a and transformed on Escherichia coli BL21(DE3) and Rosetta-gami(DE3)pLysS. The concentration of isopropyl β-d-thiogalactopyranoside (IPTG), incubation temperature, and bacterial harvesting time after IPTG induction were optimized. SCSMV-CP gene was successfully amplified with size ±855 bp, subcloned into vector expression, and expressed in insoluble fraction either in both bacterial host. Optimal protein expression of SCSMV-CP recombinant was obtained at 25°C with IPTG concentration 0.25–1.00 mM and harvested at 9–12 hours after IPTG induction in E. coliBL21(DE3), and at 30°C with IPTG concentration 0.25–1.00 mM and harvested 3–12 hours after IPTG induction in E. coli Rosetta(DE3)pLysS. SDS-PAGE analysis showed that protein size of SCSMV-CP recombinant was ±35.4 kDa.